DENTAL AND ORAL HEALTH SERVICES ON PATIENT SATISFACTION AT THE DENTAL CLINIC IN INCREASING PATIENT SATISFACTION - Jeana Lydia Maramis; Ni Made Yuliana; Farenzia Imelda Tobeonda (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background: Quality health services are one of the basic needs that everyone needs to increase satisfaction when receiving services. Patient satisfaction is an important indicator and is commonly used to measure quality in health services. There are 5 dimensions in assessing service quality, namely tangibles, reliability, responsiveness, assurance, and empathy dimensions. Problems regarding the quality of health services on patient satisfaction affect the strengths and weaknesses of health service centers, one of which is dental and oral health services. Purpose: this study aims to determine the quality of dental and oral health services on patient satisfaction at the Dental Clinic of the Sonder Health Center, Minahasa Regency, North Sulawesi Province. Method: Analytical observation with a cross sectional study approach. The sample used was 52 patients who underwent treatment at the dental clinic of the Sonder Health Center, Minahasa Regency, North Sulawesi Province, using accidental sampling as a sampling technique. Data collection techniques using a questionnaire. The results showed that the services of health workers at the dental polyclinic at the Sonder Health Center, Minahasa Regency, North Sulawesi Province in increasing patient satisfaction based on the five dimensions studied were in the satisfied category, but the assurance dimension was the most dominant. After statistical tests, it turned out that the dimensions of reliability and assurance indicated that there was a significant effect on patient satisfaction, and on the dimensions of tangibles, responsiveness, and empathy, it was stated that there was no effect on patient satisfaction.